Unprecedented : A Simple Guide to the Crimes of the Trump Campaign and Presidency - Azari, Sara (Book collections on Project MUSE., 2020)
"Unprecedented is a simple, go-to guide to the many legal issues engulfing the Donald Trump presidency"--